Phanerotoma libertinecida (Hymenoptera: Braconidae), a new species of parasitoid of Grapholita libertina (Lepidoptera: Tortricidae) associated with lingonberry (Ericaceae). Issue 2 (5th August 2015) - Goulet, H.; Hillier, N.K.; Dixon, P.L.; Larson, D.J.
Abstract: Phanerotoma libertinecida new species (Hymenoptera: Braconidae: Cheloninae) is described and put in context with the latest North American revision of the genus. The species has been reared repeatedly from Grapholita libertina Heinrich (Lepidoptera: Tortricidae), which is found on lingonberry ( Vaccinium vitis-idaea var. minor Loddiges, Loddiges, and Loddiges (Ericaceae)). Its natural history is also described.